The role of information systems in the management structure - Mallaboev Nasirjon Murodullaevich; Qozaqova Munojat Sharifjanovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Currently, information technology is the most important factor affecting the rapid development of society. Although information technology has existed at various stages of human development, the characteristic feature of today's information society is that, for the first time in the history of civilization, the effort spent on obtaining and producing knowledge is less than the expenses spent on energy, raw materials, materials, and material consumer goods. is prevailing, that is, information technologies are taking the leading place among the new technologies available. The information technology industry consists of computer, communication system, data storage, knowledge storage and related fields of activity. Information technology is becoming more and more deeply embedded in all spheres of life and becoming its driving force. Information systems mean the principles, methods and tools of information storage, search, classification and processing.